2012
DOI: 10.1021/ja212117m
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Protein Flexibility in Formation of a Stable Reaction Transition State in an α-Amylase Catalysis

Abstract: Conformational flexibility of proteins provides enzymes with high catalytic activity. Although the conformational flexibility is known to be pivotal for the ligand binding and release, its role in the chemical reaction process of the reactive substrate remains unclear. We determined a transition state of an enzymatic reaction in a psychrophilic α-amylase by a hybrid molecular simulation that allows one to identify the optimal chemical state in an extensive conformational ensemble of protein. The molecular simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 41 publications
(69 reference statements)
3
76
0
Order By: Relevance
“…These simulations also indicated that the PCEs (N23PP and G51PEKN) do not significantly alter the equilibrium fluctuations (i.e., the RMSFs) in the ternary complex or the thermally averaged DAD during the hydride transfer reaction. In our view, equilibrium conformational motions facilitate the optimization of the active site electrostatic environment (28)(29)(30)36) as well as the proximity and orientation of the reactants, leading to configurations conducive to the chemical reaction. Subtle differences in conformational sampling alter the free energy landscape (i.e., the equilibrium conformational states or ensembles) in a manner that impacts the free energy barrier and therefore the hydride transfer rate constant.…”
Section: Discussionmentioning
confidence: 99%
“…These simulations also indicated that the PCEs (N23PP and G51PEKN) do not significantly alter the equilibrium fluctuations (i.e., the RMSFs) in the ternary complex or the thermally averaged DAD during the hydride transfer reaction. In our view, equilibrium conformational motions facilitate the optimization of the active site electrostatic environment (28)(29)(30)36) as well as the proximity and orientation of the reactants, leading to configurations conducive to the chemical reaction. Subtle differences in conformational sampling alter the free energy landscape (i.e., the equilibrium conformational states or ensembles) in a manner that impacts the free energy barrier and therefore the hydride transfer rate constant.…”
Section: Discussionmentioning
confidence: 99%
“… 1 9 Moreover, these electrostatic interactions are expected to be significantly modulated by the conformational changes that occur over the catalytic cycle. 4 , 7 , 10 , 11 In particular, the electrostatic environment in the active site is likely to change as the ligands bind, the chemical reaction occurs, and the ligands are released. Quantifying the electrostatic contributions to the individual catalytic steps, as well as the impact of conformational changes on the electrostatic interactions, is a challenging yet important goal in the field of enzyme catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…15 This reorganization would play a similar role to solvent polarization in Marcus theory for electron transfer in solution, 18 although much slower conformational components could be involved in enzymatic catalysis. 12,19 In general, the coordinate that describes the transformation of the system from reactants to products is a collective coordinate that involves the degrees of freedom not only of the solute/substrate but also of the environment (the solvent and/or the enzyme).…”
mentioning
confidence: 99%
“…This has been suggested for some cases covering both fast vibrational motions 22 and slow conformational changes. 19 However, other analysis have stressed that the role of protein motions can be satisfactorily incorporated in the description of the chemical step as equilibrium fluctuations and thus explicit dynamical treatments of protein motions would be not really necessary for modeling enzymatic catalysis. 5,9,13,14,24 TST offers a convenient framework to incorporate non-statistical effects of protein motions.…”
mentioning
confidence: 99%